THE EFFECT OF PSYCHOLOGICAL CAPITAL ON WORK ENGAGEMENT WITH JOB CRAFTING AS A MEDIATOR VARIABLE AMONG GENERATION Y EMPLOYEES - Andini A.G. (Russian Journal of Agricultural and Socio-Economic Sciences, 2019)
This study aims to examine whether there is a psychological capital effect on work engagement with job crafting as a mediator variable in Generation Y employees. The definition of work engagement in this study refers to the theory revealed by Schaufeli, et al. (2002), psychological capital using the Luthans theory, et al. (2004), and job crafting using the theory of Tims, et al. (2011). The subjects in this study were 82 people with the criteria of individuals who were working and aged 20 to 36 years. The scale used in this study is the Utrecht Work Engagement Scales (UWES) which consists of 15 items, Job Crafting Scales (JCS) which consist of 18 items, and the PsyCap Questionnaire (PCS) which consists of 24 items. Data analysis use simple and multiple linear regression methods based on the mediation test analysis techniques of Baron and Kenny (1986). The results of the analysis show that job crafting mediates the influence of psychological capital on work engagement on Generation Y employees.